Cognitive Bias and its Relationship to Decision Making: the Case of Talented Secondary Students in Jeddah - Al-Dhahri, Dalal Hamid; Al-Ghamdi, Arwa Abdullah; El-Keshky, Mogeda El-Sayed (Journal of Educational and Psychological Sciences, 2020)
This study aims at investigating the relationship between cognitive biases and decision making from a sample of gifted secondary students. It also aims at identifying the level of students’ cognitive biases and decision making and the differences in these two areas based on different classrooms. Random sampling was used to collect data from 139 female secondary students from the gifted group. Their age ranged between (16-18) with an average of (16.6), A descriptive method was adopted in the study. The research tools used consisted of DACOBS David Assessment of Cognitive biases Scale (Vander Gaag. et al., 2000), translated and standardized by the present researchers, and Tuistra’s decision making scale for teenagers (Tuinstra, et al., 2000). The findings of the study show a negative correlation between cognitive biases and decision making. Also, there were no differences between cognitive biases and decision making scores based on different classrooms. The study also shows a low level of students’ cognitive biases and a high level of decision making. The study recommends activating the role of mentors and students' counseling, planning for the values and behaviors that need to be acquired by students by including them in the annual goals of the school administration and participating in societal awareness and education.
Keywords: Cognitive Biases; Decision Making; Gifted students